Hepatitis A Virus in Food Detection and Inactivation Methods - Sánchez, Glòria; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Hepatitis A virus (HAV) is responsible for around half of the total number of hepatitis infections diagnosed worldwide. HAV infection is mainly propagated via the fecal-oral route, and as a consequence of globalization, transnational outbreaks of foodborne infections are reported with increasing frequency. Therefore, in this review, state-of-the-art information on the molecular procedures for HAV detection in food, and the efficacy of common food manufacturing processes are compiled. The purpose of this Brief is to consolidate basic information on various aspects of HAV and to provide a guideline for its prevention and control across the food supply chain from pre-harvest to manufacturing.
Introduction -- Classification -- Features of hepatitis A infection -- Epidemiology -- Regulations and Recommendations -- Vaccination.- Analytical methods for HAV detection in food.- HAV extraction from food -- Nucleic acid extraction and purification.- HAV detection in food by molecular techniques.- Quality controls -- Assessment of infectivity -- HAV survival and inactivation under different food processing conditions -- Stability of HAV in food products.- HAV inactivation under different food-processing technologies -- Conclusions and future directions.
Keywords: Virology; Food—Biotechnology.; Infectious diseases; Public health; Virology; Food Science; Infectious Diseases; Public Health